Recursos Educativos Digitales Abiertos del Ministerio de Educación del Ecuador para el proceso de enseñanza dirigidos al nivel de básica elemental utilizados por los docentes de las Escuelas de Educación General Básica y Unidades Educativas Fiscales de la ciudad de Loja en el año 2022,2023 - Armijos Jimenez, Gladys Isabel (2023)
Currently, the management of educational resources is of great significance in the academic field, especially the use of open digital educational resources in the classroom, since these help the development of building and transforming their learning, which leads to define the use of the Open Digital Educational Resources (REDA) of the Ministry of Education of Ecuador for the teaching process directed at the elementary level used by teachers of the General Basic Education Schools and Fiscal Educational Units of the city of Loja in the year 2022-2023; indicating that the methodology used is based on the deductive method, with a quantitative approach of exploratory-descriptive scope. Likewise, the survey was used as a technique and an instrument was developed for the collection of information, whose population was 41 teachers from the different Educational Institutions of the city of Loja, managing to identify 24 resources of the REDA platform for the teaching process, aimed at the basic elementary level. Therefore, the 24 digital educational resources were described, based on the pedagogical information provided by the same platform. The use of digital resources was diagnosed, where in the usual scale "A new life" stands out for the area of Social Sciences "Meeting of cultures" in the area of Cultural and Artistic Education and finally "La Yincana" in the area of physical education, in occasionally "A new friendship" stood out in the area of social sciences, "The school excursion" and "We are diverse" in the area of Cultural and Artistic Education and finally for the area of physical culture, "Between iguanas and Turtles" and in never distinguished "The little mayoress", "An artist in the family ” and finally “A mystical experience”; Likewise, each of these resources was also defined taking the pedagogical information from the platform in response to the general objective. Keywords: REDA Platform, Ministry of Education of Ecuador, Open Digital Educational Resources, Basic Elementary.